Peran Country of Origin dan Loyalitas Merek Terhadap Niat Beli Ulang - Ajeng Aquinia; Euis Soliha; Ali Maskur (Jurnal Bisnis dan Ekonomi, 2021)
The aims of this research is to analyze the factors than can influence repurchase intentions, including the country of origin with the mediation of brand loyalty. Starbucks products ar the object of this study. The population in this study is Starbucks consumers in Semarang City using purposive sampling technique which has sample criteria on consumers who have consumed Starbucks products before. This study, using an instrument in the form of a questionnaire. The instrument validity test used factor analysis, and then for the reliability test, it used Cronbach's Alpha. After that, the collected data were analyzed by multiple regression analysis methods and mediation measurement using Sobel Test. The results showed that the country of origin has a positive effect on brand loyalty. However, the country of origin has no effect on repurchase intention. Brand loyalty has a positive effect on repurchase intention and is able to perfectly mediate between the country of origin and repurchase intention.